Wheel-Running Facilitates Phase Advances in Locomotor and Peripheral Circadian Rhythm in Social Jet Lag Model Mice - Oneda, Satoshi; Cao, Siyuan; Haraguchi, Atsushi; Sasaki, Hiroyuki; Shibata, Shigenobu (Frontiers in Physiology, 2022)
The circadian clock maintains our health by controlling physiological functions. Social jet lag is one factor that can disrupt the body’s clock. This is caused by the difference in sleeping hours between weekdays when we live according to social time and holidays when we live according to our body clock. The body’s clock can be altered by exercise, nutrition, and stress, and several studies have reported that these factors can be used to improve a disturbed body clock. Here we focused on exercise and examined whether continuous wheel running could improve the disordered body clock in a mouse model that mimics social jet lag. The results showed that the wheel-running exercise group showed faster synchronization of the start time of activities on weekdays when social jet lag was delayed and the forward direction of the rhythm of clock gene expression in the peripheral organs after a rapid advance in the rhythm of life. The wheel-running exercise improved the disordered body clock in the social jet lag model mice; thus, is possible that the effective inclusion of exercise in human life can improve the disordered body clock in terms of social jet lag.